2016
DOI: 10.1186/s11671-016-1498-2
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Magnetite (Fe3O4) Nanoparticles Using Seaweed (Kappaphycus alvarezii) Extract

Abstract: In this study, a simple, rapid, and eco-friendly green method was introduced to synthesize magnetite nanoparticles (Fe3O4-NPs) successfully. Seaweed Kappaphycus alvarezii (K. alvarezii) was employed as a green reducing and stabilizing agents. The synthesized Fe3O4-NPs were characterized with X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared (FT-IR), and transmission electron microscopy (TEM) techniques. The X-ray diffraction planes at (220), (311), (400), (422), (51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(123 citation statements)
references
References 37 publications
10
90
1
1
Order By: Relevance
“…Green synthesized metallic nanoparticles exhibit unique physical, thermal, chemical, and catalytic properties, [1,2] and have found great application in health care as antiplasmodial [3], anticancer, and antimicrobial [4,5], synthetic biology and cellular transportation [6]. The most important feature responsible for their wide range use is attributed to their large surface area to volume ratio, stability, biocompatibility and have a high surface energy as well as unique adsorption phenomenon [7][8][9]. In addition, metal nanoparticles are a few hundred nanometers smaller than comparable large biological molecules such as enzymes, receptors and antibodies [1].…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesized metallic nanoparticles exhibit unique physical, thermal, chemical, and catalytic properties, [1,2] and have found great application in health care as antiplasmodial [3], anticancer, and antimicrobial [4,5], synthetic biology and cellular transportation [6]. The most important feature responsible for their wide range use is attributed to their large surface area to volume ratio, stability, biocompatibility and have a high surface energy as well as unique adsorption phenomenon [7][8][9]. In addition, metal nanoparticles are a few hundred nanometers smaller than comparable large biological molecules such as enzymes, receptors and antibodies [1].…”
Section: Introductionmentioning
confidence: 99%
“…In our review of literature, different sizes have been revealed for the biosynthesized FeNPs using plants extracts. For example, 7–14 nm for T. foenum‐graecum ; 20 nm for Dioscorea opposite ; 20–70 nm for eucalyptus leaf extracts; 9.2 nm for Daphne mezereum ; 60 to 300 nm for Amaranthus dubius ; 11.0 and 20.0 nm for Seaweed of Kappaphycus alvarezii ; 40–50 nm for oolong tea extract . 7.69 nm for Platanus orientalis ; 96 to 110 nm for Azardirachta indica ; 40 to 60 nm for tea extract …”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of IONPs, 1 mole of FeCl 2 .4H 2 O and 2 moles of FeCl 3 .6H 2 O were dissolved in 100 ml sterile DW and heated at 80 °C under constant stirring conditions. To this solution, 5 ml aqueous leaf extract of Ocimum tenuiflorum was added followed by dropwise addition of NaOH solution [33,34]. Continuous stirring was carried out during the entire synthesis process to ensure uniform mixing.…”
Section: Materials and Methods Preparation And Synthesis Of Ionps Usimentioning
confidence: 99%